Unveiling the Complexity of Medication Errors: A Nursing Perspective on Contributing Factors to Medication Errors - Ebtisam Elhihi; Mohammad Hazazi; Jawaher Adam; Rudayna Al Romaili; Shahida Tasneem; Dania Fallatah; Farzana Manzoor; Fahad Almoallad; Miad Fallatah; Abdulkarim Alfahmi; Amani Albandar (Evidence-Based Nursing Research)
Context: Medication errors have long been associated with poor medical care quality, lengthy hospital stays, substantially increased medical costs, and a decline in patient confidence in the hospital's ability to provide quality care. Additionally, it is imperative to acknowledge that nurses serve as the final defense in mitigating medication errors and ensuring patient safety.